Toxic Effects of Miller on Chromosomes and Sperms of Albino Males Mice - Fattah, Yousif M.; Mustafa, Sarbast I. (Science Journal of University of Zakho, 2014)
The genotoxicity of Miller (glyphosate) herbicide was evaluated in males albino mice Mus muscles BALB/c strain. The tested parameters were chromosomal aberrations and sperm abnormalities to evaluate a possible damage effects on genetic material and sperms. The herbicide was administered orally to adult male laboratory mice in 4 different doses (0, 250, 500, and 750 mg/kg of body weight). The mice were killed at two periods: after 3 and 6 weeks. The results of chromosome aberration assay revealed that all the tested doses and periods induced structural chromosomal aberrations (CAs) such as centromeric gaps, chromatid gaps, delations, dicentric chromosomes and ring chromosomes. The results of sperm abnormality assay revealed that miller has the ability to induce sperm abnormalities in all doses used comparing to untreated mice, which represented by hookless sperm, swollen head sperm, amorphous head sperm, sperm without head, defective hook sperm, banana head sperm, double head sperm, sperm without tail, double tail sperm, bent midpiece defect and coiled tails.